Location and dynamics of the immunodominant CD8 T cell response to SIVΔnef immunization and SIVmac251 vaginal challenge. - Arun K Sasikala-Appukuttan; Hyeon O Kim; Nikilyn J Kinzel; Jung Joo Hong; Anthony J Smith; Reece Wagstaff; Cavan Reilly; Michael Piatak; Jeffrey D Lifson; R Keith Reeves; R Paul Johnson; Ashley T Haase; et al. (PLoS ONE)
Live-attenuated SIV vaccines (LAVs) have been the most effective to date in preventing or partially controlling infection by wild-type SIV in non-human primate models of HIV-1 transmission to women acting by mechanisms of protection that are not well understood. To gain insights into mechanisms of protection by LAVs that could aid development of effective vaccines to prevent HIV-1 transmission to women, we used in situ tetramer staining to determine whether increased densities or changes in the local distribution of SIV-specific CD8 T cells correlated with the maturation of SIVΔnef vaccine-induced protection prior to and after intra-vaginal challenge with wild-type SIVmac251. We evaluated the immunodominant Mamu-A1*001:01/Gag (CM9) and Mamu-A1*001:01/Tat (SL8) epitope response in genital and lymphoid tissues, and found that tetramer+ cells were present at all time points examined. In the cervical vaginal tissues, most tetramer+ cells were distributed diffusely throughout the lamina propria or co-localized with other CD8 T cells within lymphoid aggregates. The distribution and densities of the tetramer+ cells at the portal of entry did not correlate with the maturation of protection or change after challenge. Given these findings, we discuss the possibility that changes in other aspects of the immune system, including the quality of the resident population of virus-specific effector CD8 T cells could contribute to maturation of protection, as well as the potential for vaccine strategies that further increase the size and quality of this effector population to prevent HIV-1 transmission.